Performance analysis of QoS for bulk call generator via VoIP / Mohd Saufi Abdul Rahim - Abdul Rahim, Mohd Saufi (2012)
This paper diagnoses of voice quality on IP network. The weakness of VoIP as it manages voice and data service together in the same network. There are big possibilities that can affect QoS for VoIP. There a lot of category to measure QoS for VoIP application such as MOS, delay, jitter, packet loss and R factor conversational. However, this paper will focus only two VoIP QoS category - packet loss and jitter. Packet loss and jitter are two major factors that able to affect the quality of the service.